Jujitsu terminology : Japanese jujitsu martial arts terminology English to Japanese & Japanese to English translations - Hill, Tom (Andrews UK Limited, 2014)
Most of the Jujitsu terminology any student of the Japanese Martial Arts will ever need. In Japanese to English and English to Japanese. By Tom Hill; 40 years Martial Arts experience, 3rd Dan BKA (British Karate Association), 4th Dan Academy of Goju Ryu, 6th Dan Shotokan; Jin Sei Kai, 8th Dan Goju.co.uk & Chief instructor, Special Advisor to; Combat Jujitsu Hellas.